2016
DOI: 10.15835/nsb.8.2.9807
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Nitric Oxide on High Temperature Induced Oxidative Stress in Wheat (<i>Triticum aestivum</i>) Callus Culture

Abstract: High temperature (HT) stress is a major environmental factor that limits plant growth, metabolism and productivity worldwide. Plant growth and development involve numerous biochemical reactions that are sensitive to temperature. Plants' responses to HT vary with the degree and duration of HT and the plants' adaptability. The protective effect of exogenous nitric oxide in alleviating high temperature induced damages of wheat (Triticum aestivum) callus tissues was investigated. Heat treatment (35 and 40 °C) alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This protective effect of NO may be associated with its role as antioxidant and by directly scavenging ROS such as O 2 − , to form peroxynitrite anion (ONOO − ), which is less toxic than H 2 O 2 or by inhibiting NADPH oxide and reducing ROS production [ 44 , 45 , 46 ]. The earlier studies have shown that NO prevents ROS generation and lipid peroxidation in the plants grown under high temperature stress [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect of NO may be associated with its role as antioxidant and by directly scavenging ROS such as O 2 − , to form peroxynitrite anion (ONOO − ), which is less toxic than H 2 O 2 or by inhibiting NADPH oxide and reducing ROS production [ 44 , 45 , 46 ]. The earlier studies have shown that NO prevents ROS generation and lipid peroxidation in the plants grown under high temperature stress [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide can enhance such effects. The example of wheat plants shows an increase in the activity of SOD, catalase, guaiacol peroxidase, ascorbate peroxidase, glutathione reductase under heat stress as a result of pretreatment of plant objects with NO donor SNP ( Karpets et al., 2011 ; El-Beltagi et al., 2016 ). Under prolonged heat stress, SOD, catalase, ascorbate peroxidase, and glutathione reductase activities increased in wheat treated with SNP ( Iqbal et al., 2022 ).…”
Section: Influence Of Gasotransmitters On Functioning Of Plant Protec...mentioning
confidence: 99%
“…The most demonstrated ability of NO in reducing ROS levels is by enhancing antioxidant enzyme activities under unfavorable temperatures (Neill et al, 2002 ; Karpets et al, 2011 ). For instance, stimulation of ascorbate peroxidase and glutathione reductase enzyme activities by heat stress-induced NO signal in T. aestivum plays an important role in the metabolism of H 2 O 2 (El-Beltagi et al, 2016 ). Likewise, 0.5 mM SNP-activated antioxidant enzymes superoxide dismutase, catalase and soluble peroxidase, were positively correlated with elevated tolerance in T. aestivum coleoptiles heat shocked at 43°C for 10 min (Karpets et al, 2011 ).…”
Section: No As Antioxidantmentioning
confidence: 99%